PRODUCTION OF Y2O3 COATED AL2O3 REINFORCED ALUMINIUM MATRIX COMPOSITES AND THE COATING OF INTERFACE EFFECTS OVER WETTABILITY PROPERTIES - Altuner, Serdar; Kelesoglu, Ergun (YILDIZ TECHNICAL UNIV, 2012)
Usage of Aluminium metal matrix komposites have been increased in automotive and areospace industry due to physical and mechanical properties of these. Requested properties have been obtained depends on particle's different particle size and amount is added into matris. In this study, 5-10-15 and 20 % Al2O3 particle has been used as reinforcement. The wettability of Al2O3 is weak by molten aluminium. Weak bond force between aluminium and Al2O3 effects final properties of composite and decrease mechanical properties of it. In order to cope with this problem, Al2O3 powder was coated by Y2O3 and then it was added into aluminium. The aim of this study is the improvement of wettability using by Y2O3 coated Al2O3 particle reinforced aluminium matrix composites produced by squeze casting method so that mechanical properties will be enhanced. Produced composite's density, hardness and wear behaviour is examined and analysed SEM microstructle. It was aware that during increasing reinforced volume, hardness of MMC was increased, coefficient of friction was decreased so wear resistance was improved.
Keywords: Aluminium matrix composites; wettability; interface; Y2O3 interface coating; Engineering